2019
DOI: 10.1212/wnl.0000000000006950
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and skeletal muscle effects in the randomized HOPE-Duchenne trial

Abstract: ObjectiveTo assess the feasibility, safety, and efficacy of intracoronary allogeneic cardiosphere-derived cells (CAP-1002) in patients with Duchenne muscular dystrophy (DMD).MethodsThe Halt Cardiomyopathy Progression (HOPE)-Duchenne trial is a phase I/II, randomized, controlled, open-label trial (NCT02485938). Patients with DMD >12 years old, with substantial myocardial fibrosis, were randomized (1:1) to usual care (control) or global intracoronary infusion of CAP-1002 (75 million cells). Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 36 publications
(43 reference statements)
0
54
0
1
Order By: Relevance
“…Given the preclinical insights reported here, CDCs are now being administered systemically in a placebo-controlled trial in DMD patients (HOPE-2; ClinicalTrials.gov Identifier: NCT03406780), thereby avoiding the need for cardiac catheterization as performed in the previous HOPE-Duchenne trial (31). In addition to CDCs themselves, EXOs derived from CDCs are a promising next-generation therapeutic candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Given the preclinical insights reported here, CDCs are now being administered systemically in a placebo-controlled trial in DMD patients (HOPE-2; ClinicalTrials.gov Identifier: NCT03406780), thereby avoiding the need for cardiac catheterization as performed in the previous HOPE-Duchenne trial (31). In addition to CDCs themselves, EXOs derived from CDCs are a promising next-generation therapeutic candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Due to small sample sizes, statistical tests for comparison were not performed. Categorical data presented as total count and percentage (%), and continuous data are presented as mean ± standard deviation (SD) These anti-inflammatory effects have been demonstrated in animal models of myocardial ischemia, myocarditis, muscular dystrophy, aging, heart failure with preserved ejection fraction, pulmonary arterial hypertension and dilated cardiomyopathy [3,20,21,33,34,42]. Finally, based on preclinical work, a majority of IV CDCs are retained in the lungs [6].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiospheres are agglomerates of several cell types, predominantly MSC, harvested from the right ventricle by an endomyocardial biopsy (Smith et al, 2007) with a subsequent intracoronary delivery while c-kit + CSC are grown from a right appendage biopsy taken during a coronary artery bypass operation before being also reinjected into the coronary arteries. However, the first have failed to show benefits in an ischemic cardiomyopathy phase II trial which was prematurely interrupted in April, 2017 for futility; however, the use of these cells in Duchenne muscular dystrophy has yielded an encouraging efficacy signal (Taylor et al, 2019) which needs to be confirmed by the ongoing HOPE-II study, planned to randomize 84 non-ambulatory and ambulatory patients with Duchenne muscular dystrophy to intravenous infusions of either 150 million cardiosphere-derived cells every 3 months for a total of 4 doses or placebo. The use of c-kit + CSC has been largely based on preclinical data now considered to be in part fraudulent 1 and there is some consensus that these cells are rather endowed with an angiogenic potential (van Berlo et al, 2014).…”
Section: Why Pluripotent Stem Cells?mentioning
confidence: 99%